2016
DOI: 10.1128/jvi.01004-16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants Directing HIV-1 Gag Assembly to Virus-Containing Compartments in Primary Macrophages

Abstract: The subcellular sites of HIV-1 assembly, determined by the localization of the structural protein Gag, vary in a cell-type-dependent manner. In T cells and transformed cell lines used as model systems, HIV-1 assembles at the plasma membrane (PM). The binding and localization of HIV-1 Gag to the PM are mediated by the interaction between the matrix (MA) domain, specifically the highly basic region, and a PM-specific acidic phospholipid, phosphatidylinositol-4,5-bisphosphate [PI(4,5)P 2 ]. In primary macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 106 publications
0
7
1
Order By: Relevance
“…Previous studies have shown that NC deletion abrogates Gag localization to specific PM domains, such as uropods in polarized T cells or the virus-containing compartments (VCCs) in macrophages, whereas insertion of LZ restores such localization (71,72). In contrast, we do not see a difference in the subcellular localization of Gag between full-length Gag and delNC Gag for any of the MA mutants examined (Fig.…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies have shown that NC deletion abrogates Gag localization to specific PM domains, such as uropods in polarized T cells or the virus-containing compartments (VCCs) in macrophages, whereas insertion of LZ restores such localization (71,72). In contrast, we do not see a difference in the subcellular localization of Gag between full-length Gag and delNC Gag for any of the MA mutants examined (Fig.…”
Section: Discussioncontrasting
confidence: 76%
“…Thus, the combination of RNA labeling techniques with the HIV-1 Gag-iFRET system would provide a unique method in this context to elucidate the dynamics of Gag-viral RNA release from the budding site into progeny virions. Moreover, viral assembly appears to be cell-type dependent ( Ono and Freed, 2004 ), and virions are assembled and released in viral-containing compartments (VCCs) in macrophages, beyond the reach of antivirals or antibodies, and from where cell-to-cell infection can occur unhindered ( Pelchen-Matthews et al, 2003 ; Sharova et al, 2005 ; Gousset et al, 2008 ; Groot et al, 2008 ; Chu et al, 2012 ; Inlora et al, 2016 ). HIV-1 Gag-iFRET could be used in live-cell imaging to localize and visualize maturation in various cellular compartments in different cell-type settings.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to elucidate the role of the viral factors dictating the assembly site of HIV in macrophages, Inlora and colleagues evaluated the impact of targeted deletions or mutations in the different Gag domains, on virion assembly at the VCC ( 118 ). Viral mutants unable of high-order multimerization, due to NC substitutions, distributed equally between the VCC and the cell surface ( 118 ). This indicates that Gag initially binds the membrane arbitrarily at the surface membrane or the VCC and initiates low-order multimerization.…”
Section: Cell Biology Of Hiv Assembly In Macrophages: From Gag Synthementioning
confidence: 99%